Ganzheitliche Verkehrserziehung für Kinder und Jugendliche. Teil 5: Radfahrausbildung Sekundarstufe I. - Voll, Stefan; Moritzer, Larissa; Gehlert, Tina (My University, 2020)
Das hier beschriebene Projekt beschreibt ein weiterführendes Radfahrtraining für die Sekundarstufe I. Den Ausgangspunkt der Überlegungen stellen die aktuellen Unfallzahlen von Kindern und Jugendlichen im Straßenverkehr im Alter zwischen 10 und 14 Jahren dar. Die Zielgruppe, das Setting sowie die Durchführung werden im beschrieben. Anschließend werden die Entwicklung der exekutiven kognitiven Funktionen sowie der aktuelle wissenschaftliche Stand des Fahrradtrainings beleuchtet. Danach wird das Konzept, bezogen auf allgemeine und spezielle Übungsformen, vorgestellt. Die praktische Erprobung an einer bayerischen Mittelschule wird hinsichtlich der teilnehmenden Schülerinnen und Schüler sowie praktischen Erfahrungen aufgezeigt. Abschließend folgen auf Basis der empirischen Untersuchung, mittels zweier theoretischer und eines praktischen Tests, die Darstellung der Ergebnisse sowie praktische Hinweise für die schulische Umsetzung. Das Trainingskonzept, inklusive detaillierter Ablaufpläne, Durchführungshinweisen und Umsetzungsvarianten, ist in einem separaten Bericht dokumentiert. (Forschungsbericht / Gesamtverband der Deutschen Versicherungswirtschaft Nr. 69).

Almost every second young person between 10 and 15 years involved in accident was cycling. At this age, the bicycle becomes an important means of transport for independent mobility. School trips in particular are often made by bicycle. In Germany, children in their third and fourth year of primary school already receive a basic cycling training. It is an established part of road safety education at schools, but is not sufficient. For this reason, the present project aims to develop and to test a further cycling training for pupils in secondary schools. The training is based on research on the development of higher cognitive functions (the executive functions), training development in general and bicycle training in particular. The aim is to improve young cyclists ability to cope with the demands of especially of complex traffic situations. The training consists of 10 units of 90 minutes each. Each unit contains general exercises for cognitive activation and bike-specific exercises. The For safety reasons the training is not carried out in real traffic, but on designated areas such as sports ground, school yards etc. Following the training development, testing took place at a Bavarian secondary school. An empirical preliminary study was also conducted in preparation for a comprehensive evaluation. In this research report, the scientific basis of the bicycle training is presented as well as how it fits with the target group. First experiences with the training in a school setting are reported as well as the results of the empirical preliminary study are reported. It shows that this training program can be integrated very well into the everyday school life. The results of the empirical preliminary study indicate a training-specific improvement for controlling the bike after the training, but the methodological validation is not yet sufficient. The training concept, including detailed schedules, implementation instructions and implementation variants, is documented in a separate report. (Forschungsbericht / Gesamtverband der Deutschen Versicherungswirtschaft Nr. 69)
Keywords: Fahrradverkehr; Kind; Jugendlicher; Straßenverkehr; Verkehrsteilnehmer; Verkehrserziehung; Verkehrssicherheit; Mittelschule; Empirische Untersuchung; Radfahrtraining